2005
DOI: 10.1073/pnas.0409308102
|View full text |Cite
|
Sign up to set email alerts
|

Loss of perivascular aquaporin 4 may underlie deficient water and K + homeostasis in the human epileptogenic hippocampus

Abstract: An abnormal accumulation of extracellular K ؉ in the brain has been implicated in the generation of seizures in patients with mesial temporal lobe epilepsy (MTLE) and hippocampal sclerosis. Experimental studies have shown that clearance of extracellular K ؉ is compromised by removal of the perivascular pool of the water channel aquaporin 4 (AQP4), suggesting that an efficient clearance of K ؉ depends on a concomitant water flux through astrocyte membranes. Therefore, we hypothesized that loss of perivascular A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
198
3
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 253 publications
(230 citation statements)
references
References 31 publications
11
198
3
11
Order By: Relevance
“…Tissue samples of MTS have been shown to present a striking lack of peri‐vascular AQP4 water channels that mediates the glymphatic water clearance (Eid et al., 2005). The absence of AQP4 channels in MTS areas could lead to altered extracellular electrolyte concentrations that sensitizes neuronal tissue to seizures (Eid et al., 2005; Lundgaard et al., 2017; Marchi et al., 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Tissue samples of MTS have been shown to present a striking lack of peri‐vascular AQP4 water channels that mediates the glymphatic water clearance (Eid et al., 2005). The absence of AQP4 channels in MTS areas could lead to altered extracellular electrolyte concentrations that sensitizes neuronal tissue to seizures (Eid et al., 2005; Lundgaard et al., 2017; Marchi et al., 2007). …”
Section: Discussionmentioning
confidence: 99%
“…In sclerotic hippocampi the expression of AQP4 on the perivascular membrane of the astrocyte is reduced, whereas its expression remains unchanged on the membrane facing the neuropil, thus suggesting a probable decrease in the expulsion of water from the neuropil out to the blood vessel lumen. 25 …”
Section: Astrocyte Transporter Moleculesmentioning
confidence: 99%
“…K ϩ and water are taken up by the astrocyte membrane facing the neuropil and pushed into the blood and CSF through the end foot membranes under conditions of high neuronal activity. 96 A loss of AQP4 from the perivascular membrane could impair water movements 25 and lead to increased extracellular concentrations of K ϩ , which can depolarize neurons in adjacent regions such as the subiculum. This buffering of K ϩ is probably performed by the GFAP positive subset of GluT-like astrocytes.…”
Section: Astrocytes May Contribute To the High Glutamate Levels At Thmentioning
confidence: 99%
“…11 Several evidences demonstrated that the epileptic seizures alter bloodbrain barrier (BBB) properties and permeability. 31,54,117 Particularly, a recently in vivo study demonstrated the dynamic changes of BBB permeability during epileptogenesis. The long-lasting increased permeability of the BBB indicated that it may contribute to increased excitability in the epileptogenic foci, leading to the progression of epilepsy and seizure development.…”
Section: Epilepsymentioning
confidence: 99%